A perspective on oil spills: What we should have learned about global warming. (1st March 2021) - Little, David I.; Sheppard, Stephen R.J.; Hulme, David
Abstract: Scientific knowledge of marine pollution and oil spill response (OSR) innovation has diffused over half a century. Local community resilience to spills and the equitable application of knowledge worldwide are constrained by several barriers. These range from access, governance, cost minimisation, through austerity and poverty in affected areas, to realpolitik (e.g. vested interests, nationalism, corruption, security breakdown and war). Ongoing incidents show inequalities in spill risk and OSR capability. Advances in knowledge have belatedly brought us to the conclusion that the logical way to reduce adverse impacts of oil in an era of global warming is to accelerate decarbonisation. This would rapidly and simultaneously reduce the frequency, magnitude and consequences of oil spills. Meanwhile, mitigating spills, managing OSR, and restoring local communities and ecosystems at spill sites are fundamental obligations for the oil industry. These obligations should be routinely enforced by all responsible governments, and backed by inter-governmental agencies and conventions. However, we must no longer assume that even the best practices in exploration, production, refining, transport and consumption of hydrocarbons can adequately reduce their leading role in the ongoing destruction of the global environment. Graphical abstract: Image 1 Highlights: Oil 'spilled' by all of us into the air by combustion drives runaway climate change. Contingency planning and response are necessary tools but not sufficient everywhere. Spills were landmarks to the global warming crisis and the need for decarbonisation. Despite widespread multilateral values we can be disabled by climate change denial. Access to social justice mitigates vulnerability both to spills and climate change.